DESAIN DAN PEMBUATAN PERANGKAT PELUBANG PORTABEL RUMAH ANAK KUNCI PADA KERANGKA ALUMINIUM HOLLOW - Syamsul Hadi; Bambang Irawan; Purwoko Purwoko; Anggit Murdani; Fica Aida Nadhifatul Aini; Cahyo Tri Waluyo (P3M Politeknik Negeri Malang, 2024)
Manual work using drilling machines, manual grinding, and filing in penetrating holes in the profile of the hollow Aluminum frame in the shape of the glass door lock housing is the problem faced. Community service aims to obtain a portable door lock children's home hole prototype for hollow aluminum frame profiles for glass doors. The method applied is design discussions with partners, making a hole punch frame for a portable door lock housing for an Aluminum frame profile according to the dimensions of a 3 Ton jack, making a punch in the exact shape of a particular key housing hole with an electric discharge machine (EDM) Wire Cut, hardening and tempering steel punch, making sharp side profiles for the shape of the key housing using a CNC milling machine, trial of punching the door frame profile, and handing over the portable door lock home punch tool kit to the service partner. With the completion of the manufacture of the portable door lock children's home punch tool kit as a work aid, it can be used to support the production of glass door frames ordered by the wider community with good results, a fast process, and production costs can be reduced. In this way, there is a synergy between State Polytechnic of Malang (Polinema) and community members in the production of products needed by the community more efficiently and able to meet the needs of the general community.